Pengaruh Pendidikan, Pelatihan terhadap Pengembangan Pegawai di Badan Pengembangan Kepegawaian & Sumber Daya Manusia Kabupaten Kepulauan Sula - Asri Fokaaya; Marwan Marwan; Milwan Milwan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to determine the effect of education and training on the career development of civil servants at the personnel agency and human resource development in the Sula archipelago district. This study focused on employees of the Personnel & Human Resources Development Agency of the Sula Islands Regency, the sample used was 107 people. Data was collected through a questionnaire, then the variables were measured using a Likert scale. Data analysis was done by using multiple regression analysis method. The software used for analysis is SPPS. 20. From the standard estimates for the variables Education (X1), Training (X2), Career Development (Y), an equation can be made, namely Y = 1.977+ 0.308 (X1) + 0.220 (X2)+e. This study concludes that the education variable has a coefficient value of 0.220 and has a significance value of 0.002 variable which is considered constant. The training variable shows a value of 0.220 and has a significance value of 0.021. simultaneously shows that the two variables of education and training have a significance probability of 0.000 which simultaneously affects the career development variable.